PATRON-CLIENT RELATIONSHIP PATTERN IN FISHERY BUSINESS CATCH IN DUDEPO PORT, BOLAANG UKI DISTRICT SOUTH BOLAANG MONGONDOW REGENCY - Erlansyah, Erlansyah; Djalil, Mukhlisnah; Hasani, Mohamad Pidra (Jurnal Perikanan Unram, 2025)
The rapid activity of increasing fishing productivity creates an intense relationship called patron and client between ship owners and ship workers who are often in conditions of uncertainty or unequal relations. The aim of this research is to determine relationship patterns, supporting factors and inhibiting factors in patron-client relationships in fisheries businesses. The research method used is a case study by examining phenomena comprehensively, intensely, in detail and in depth. The data analysis used is qualitative analysis using three stages including; data reduction, data presentation, and drawing conclusions. The research results show that the patron-client relationship at Dudepo Port is a relationship of reciprocity or exchange in both economic and non-economic forms. For example Patron; Apart from providing wages to clients for their services and energy, they also provide living space in the form of housing, political protection and other social assistance. There are three supporting factors for patron-client relationships, namely; kinship, trust, and remuneration. Meanwhile, factors inhibiting patron-client relations are the price of fish, patron superiority, and profit sharing.